Spatial distribution and pollution evaluation of heavy metals in soils surrounding a typical municipal solid waste incineration plant in Hang-Jia-Hu plain. (2017) - Zhong, Shan; Gao, Hui; Zhang, Lishan; Su, Hongfeng; Zhang, Cheng
In this study, soil samples around the typical municipal solid waste incineration (MSWI) plant in Hangzhou-Jiaxing-Huzhou Plain were collected. The concentrations of heavy metals were determined using X-ray fluorescence spectrometry (XRF), atomic absorption spectrometry (AAS) and mercury analyser. Mean concentrations of Cr, Mn, Cu, Pb and Fe were 174, 708, 47.68, 41.95 and 39, 058 mg/kg in this region, respectively. Principal component analysis and cultural enrichment factor (CEF) analysis showed that Cr, Mn and Fe were present as background origin in soils surrounding the incineration plant. Combined with historic land use information, the results showed that the application of pesticide with high content of Cu probably contributed to Cu distributions in the study region. The MSWI plant with high Pb emission from stack resulted in the Pb distribution patterns in surrounding soils. The study highlighted that MSWI could contribute to heavy metal accumulation in surrounding soil.